IGMN: An Incremental Gaussian Mixture Network that Learns Instantaneously from Data Flows - Heinen, Milton Roberto; Engel, Paulo Martins; Pinto, Rafael C. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2011: Anais do VIII Encontro Nacional de Inteligência Artificial, 2011)
This works proposes IGMN (standing for Incremental Gaussian Mixture Network), a new connectionist approach for incremental concept formation and robotic tasks. It is inspired on recent theories about the brain, specially the Memory-Prediction Framework and the Constructivist Artificial Intelligence, which endows it with some unique features that are not present in most ANN models such as MLP and GRNN. Moreover, IGMN is based on strong statistical principles (Gaussian mixture models) and asymptotically converges to the optimal regression surface as more training data arrive. Through several experiments using the proposed model it is demonstrated that IGMN is also robust to overfitting, does not require fine-tunning its configuration parameters and has a very good computational performance, thus allowing its use in real time control applications. Therefore, IGMN is a very useful machine learning tool for incremental function approximation.